A new species and new records of Melittiini from China and Vietnam (Lepidoptera, Sesiidae) - Kallies, Axel; Arita, Yutaka; Min, Wang (Zootaxa, 2016)
We review the Melittiini fauna of mainland China and list a total of 14 species in two genera. Melittia proxima Le Cerf, 1917, Melittia fulvipes Kallies & Arita, 2004, Melittia distincta Le Cerf, 1916, and Macroscelesia vietnamica Arita & Gorbunov, 2000 are recorded from China for the first time. Macroscelesia perlucida Kallies & Arita, sp. nov. is described as new to science based on specimens collected in China (Guangxi Province) and in northern Vietnam. Melittia formosana Matsumura, 1911 is considered a subspecies of Melittia eurytion (Westwood, 1848) (stat. nov.), and Melittia eurytion nagaii Arita & Gorbunov, 1997 is treated as a junior subjective synonym of M. eurytion formosana (syn. nov.).